The Israeli CIO's journey – From insourcing to outsourcing and back. Issue 3 (4th May 2019) - Aspir, Tal; Gafni, Ruti; Gordoni, Galit
ABSTRACT: One of the difficult decisions that a Chief of Information Manager takes is whether to use organisational resources or to contract suppliers, in order to perform information technology (IT) projects. Over the last decade, managers in Israel have moved from insourcing to outsourcing due to different reasons, mainly to reduce costs and focus on their core business. In the last two years, they started to return IT projects, services, and activities back, using new source models. This study examines the tendency of the Israeli IT managers in sourcing decisions in order to understand the problems, application and suitability of various kinds of models.